Impact of Center Experience on Patient Radiation Exposure During Transradial Coronary Angiography and Percutaneous Intervention: A Patient‐Level, International, Collaborative, Multi‐Center Analysis. Issue 6 (June 2016) - Simard, Trevor; Hibbert, Benjamin; Natarajan, Madhu K.; Mercuri, Mathew; Hetherington, Simon L.; Wright, Robert; Delewi, Ronak; Piek, Jan J.; Lehmann, Ralf; Ruzsa, Zoltán; Lange, Helmut W.; Geijer, Håkan; et al.
Abstract : Background: The adoption of the transradial (TR) approach over the traditional transfemoral (TF) approach has been hampered by concerns of increased radiation exposure—a subject of considerable debate within the field. We performed a patient‐level, multi‐center analysis to definitively address the impact of TR access on radiation exposure. Methods and Results: Overall, 10 centers were included from 6 countries—Canada (2 centers), United Kingdom (2), Germany (2), Sweden (2), Hungary (1), and The Netherlands (1). We compared the radiation exposure of TR versus TF access using measured dose‐area product (DAP). To account for local variations in equipment and exposure, standardized TR:TF DAP ratios were constructed per center with procedures separated by coronary angiography (CA) and percutaneous coronary intervention (PCI). Among 57 326 procedures, we demonstrated increased radiation exposure with the TR versus TF approach, particularly in the CA cohort across all centers (weighted‐average ratios: CA, 1.15; PCI, 1.05). However, this was mitigated by increasing TR experience in the PCI cohort across all centers ( r =−0.8; P =0.005). Over time, as a center transitioned to increasing TR experience ( r =0.9; P =0.001), a concomitant decrease in radiation exposure occurred ( r =−0.8; P =0.006). Ultimately, when a center's balance of TR to TF procedures approaches 50%, the resultant radiation exposure was equivalent. Conclusions: The TR approach is associated with a modest increase in patient radiation exposure. However, this increase is eliminated when the TR and TF approaches are used with equal frequency—a guiding principle for centers adopting the TR approach.